Cognitive Reserve Proxies Do Not Differentially Account for Cognitive Performance in Patients with Focal Frontal and Non-Frontal Lesions. (21st September 2020) - MacPherson, Sarah E.; Allerhand, Michael; Gharooni, Sarah; Smirni, Daniela; Shallice, Tim; Chan, Edgar; Cipolotti, Lisa
Abstract: Objective: Cognitive reserve (CR) suggests that premorbid efficacy, aptitude, and flexibility of cognitive processing can aid the brain's ability to cope with change or damage. Our previous work has shown that age and literacy attainment predict the cognitive performance of frontal patients on frontal-executive tests. However, it remains unknown whether CR also predicts the cognitive performance of non-frontal patients. Method: We investigated the independent effect of a CR proxy, National Adult Reading Test (NART) IQ, as well as age and lesion group (frontal vs. non-frontal) on measures of executive function, intelligence, processing speed, and naming in 166 patients with focal, unilateral frontal lesions; 91 patients with focal, unilateral non-frontal lesions; and 136 healthy controls. Results: Fitting multiple linear regression models for each cognitive measure revealed that NART IQ predicted executive, intelligence, and naming performance. Age also signiﬁcantly predicted performance on the executive and processing speed tests. Finally, belonging to the frontal group predicted executive and naming performance, while membership of the non-frontal group predicted intelligence. Conclusions: These ﬁndings suggest that age, lesion group, and literacy attainment play independent roles in predicting cognitive performance following stroke or brain tumour. However, the relationship between CR and focal brain damage does not differ in the context of frontal and non-frontal lesions.